2012
DOI: 10.1200/jco.2012.30.4_suppl.578
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of relapse-free survival in T3N0 colon cancer: The role of chemotherapy—A multicentric retrospective analysis.

Abstract: Background: Adjuvant chemotherapy (AC) in Stage II Colon Cancer (CC) is still under debate. Choice should be based on patients and disease characteristics. According to guidelines AC should be considered in high-risk T3N0 patients. No data are available for better option in low-risk patients. The aim of the study is to retrospectively evaluate relapse-free survival (RFS) and disease-free survival (DFS) according to treatment received in T3N0 CC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The differences between groups were not statistically significant (p = 0.426). Grande et al 28 found statistically significant differences in favor of the use of chemotherapy in terms of overall survival and of five-year DFS, however Kumar et al 30 found that the use of chemotherapy was associated with worse DFS and DSS.…”
Section: Discussionmentioning
confidence: 97%
“…The differences between groups were not statistically significant (p = 0.426). Grande et al 28 found statistically significant differences in favor of the use of chemotherapy in terms of overall survival and of five-year DFS, however Kumar et al 30 found that the use of chemotherapy was associated with worse DFS and DSS.…”
Section: Discussionmentioning
confidence: 97%
“…It is noteworthy that 5-year overall survival (OS) for all stage II patients was 81%, low-risk stage II patients without adjuvant chemotherapy had a 5-year OS of only 68%, whereas for those receiving it, OS was 86% [20]. One Italian study concentrating solely on pT3N0 reported that adjuvant-treated (AC) patients did much better than did those without it, with no major differences between low-and high-risk (RFS for AC low-risk 87% and high-risk 83%, versus no AC low-risk 75%, high-risk 71%) [21]. As their recurrence rate was markedly higher for those without adjuvant chemotherapy, these authors asked whether all stage II patients should be offered therapy.…”
Section: Most Stage II Patients Should Not Be Offered Adjuvant Chemotmentioning
confidence: 99%